The Gulag System in Northern Siberia: The Creation and Evolution of Vorkuta, Norilsk, and Kolyma. - Austin, Elizabeth (University of Virginia, 2017)
The Gulag system in the Soviet Union was created to achieve two main purposes: one, to catapult the economy into industrialization, and two, to incarcerate people likely to be a threat to the regime and actual criminals. The Gulag system was officially active from 1923 through 1960 but had long-lasting effects that are visible today. Among the areas of greatest transformation during this time period was Northern Siberia. Three of the largest and most notorious camp complexes in Northern Siberia were Vorkuta, Norilsk, and Kolyma. The camps in these areas transformed the land and economy of the area as prisoners were forced to live in these previously uninhabited locations and mine the valuable natural resources. Due to the remote locations, among the most deadly and dangerous criminals, and the most feared political prisoners were sent to these three camp complexes. Vorkuta, Norilsk, and Kolyma are known for their high death tolls as well as their contributions of natural resources to the revitalization of the Soviet Union’s economy. Why were these specific locations chosen as labor camps? How did these camp complexes start and transition into integral parts of the Gulag system and Soviet economy? How did the Gulag system change the geography, economy, and environment of these particular areas? What was working in these specific Gulag camps like? What types of prisoners were sent to these areas and what were the typical everyday conditions? Great strides have been made to understand the complexity of the Gulag system and the functions of the Gulag camp complexes of Vorkuta, Kolyma and Norilsk. Previously, historians have examined these camps individually, or the Gulag system as a whole, but the similarities between these three camps and their role in Soviet Union are too strikingly similar to ignore. The formation of these camps in Northern Siberia transformed Russia’s landscape and created cities that exist to this day because of the work of prisoners of the Gulag system. The following chapters hope to explain the similarities between these three Gulag camp complexes in Northern Siberia and explore the function of these labor camps from their formation, through to their closing.